The selective permeability barrier in the nuclear pore complex - Li, Christina (Nucleus, 2016)
The nuclear pore complex (NPC) mediates the shuttle transport of macromolecules between the nucleus and cytoplasm in eukaryotic cells. The permeability barrier formed by intrinsically disordered phenylalanine-glycine-rich nucleoporins (FG-Nups) in the NPC functions as the critical selective control for nucleocytoplasmic transport. Signal-independent small molecules (< 40 kDa) passively diffuse through the pore, but passage of large cargo molecules is inhibited unless they are chaperoned by nuclear transport receptors (NTRs). NTRs are capable of interacting with FG-Nups and guide the cargos to cross the barrier by facilitated diffusion. The native conformation of the FG-Nups permeability barrier and the competition among multiple NTRs interacting with this barrier in the native NPCs are the 2 core questions still being highly debated in the field. Recently, we applied high-speed super-resolution fluorescence microscopy to map out the natural structure of the FG-Nups barrier and determined the competition among multiple NTRs as they interact with the barrier in the native NPCs. In this extra-view article, we will review the current understanding in the configuration and function of FG-Nups barrier and highlight the new evidence obtained recently to answer the core questions in nucleocytoplasmic transport.